Mean platelet volume, platelet count, and neutrophil/lymphocyte ratio in drug-naïve patients with schizophrenia: a cross-sectional study - Cabello-Rangel, Héctor; Basurto-Morales, Marisol; Botello-Aceves, Elizabeth; Pazarán-Galicia, Osiris (Frontiers in Psychiatry, 2023)
Introduction. Mean platelet volume (MPV), platelet count and neutrophil/lymphocyte ratio have been proposed to be biomarkers of the chronic inflammatory process in schizophrenia and indicative of increased cardiovascular risk. Objective: To describe MPV, total platelet count (PLT) and neutrophil/lymphocyte ratio (NLR) between healthy controls and patients with schizophrenia, and to determine the correlation between these parameters and duration of untreated psychosis (DUP). Methods. Retrospective cross-sectional study. We included 175 patients with schizophrenia who had never received psychiatric treatment and who had undergone blood biometry and blood chemistry within 24 hours of admission. Laboratory studies were determined by the impedance method on Coulter ac-T 5diff hematological equipment. Results. MPV levels were higher than in healthy controls, but not statistically significant. The ROC curve for this parameter shows that the optimal cut-off point of agreement was 8.95 fL, with sensitivity and specificity for schizophrenia of 52% and 67% respectively, the area under the curve (AUC) was 0.580 (p= 0.079). DUP had no significant correlation with the blood parameters analyzed. Conclusion. The results partially support the hypothesis that MPV, platelet count and NLR is related to schizophrenia, and further research is needed to establish whether there is an underlying chronic inflammatory process.